1976
DOI: 10.1093/nar/3.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of single base oligonucleotides by ribonucleic acid-directed deoxyribonucleic acid polymerase

Abstract: The synthesis of DNA products complementary to artificial templates by the enzyme RNA-directed DNA polymerase isolated from avian myeloblastosis virus has been studied. Of the single base polyribonucleotides, poly(rC), poly(rA), and poly(rI) were active while poly(rG) and poly(rU) were almost inactive. The minimum length showing activity for an oligo(rC) template was 9; the minimum primer length of oligo(dG) was 3 or 4. In order to examine the fidelity of transcription, single base oligoribonucleotides of defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…The pulse-quench experiment showed that the only products formed were those consistent with utilization of the 15-nt oligo(dT) primer. Moreover, 30 24.6 Ϯ 2.8 9.1 Ϯ 0.5 dT 10 /rA 16 122 Ϯ 44 4.8 Ϯ 0.9 dT 15 /rA 16 38.2 Ϯ 8. pol and incubated at 37°C for 5 min. The reaction volume was 50 l. B, reactions were performed as described above with poly(rC), oligo(dG) n , and GTP.…”
Section: Primer Length and Sequence Composition Modulate The Rate Of 3dmentioning
confidence: 97%
See 4 more Smart Citations
“…The pulse-quench experiment showed that the only products formed were those consistent with utilization of the 15-nt oligo(dT) primer. Moreover, 30 24.6 Ϯ 2.8 9.1 Ϯ 0.5 dT 10 /rA 16 122 Ϯ 44 4.8 Ϯ 0.9 dT 15 /rA 16 38.2 Ϯ 8. pol and incubated at 37°C for 5 min. The reaction volume was 50 l. B, reactions were performed as described above with poly(rC), oligo(dG) n , and GTP.…”
Section: Primer Length and Sequence Composition Modulate The Rate Of 3dmentioning
confidence: 97%
“…Both the duration of linearity and the reaction end points differed substantially when the kinetics of nucleotide incorporation into dT 15 /rA 16 (Fig. 3A) was compared with that into dT 15 /rA 30 (Fig. 3B) or dG 15 /rC 30 (Fig.…”
Section: Primer Length and Sequence Composition Modulate The Rate Of 3dmentioning
confidence: 99%
See 3 more Smart Citations